Módulos de potência híbridos IGBT de silício e MOSFET de carbeto de silício em paralelo - Marco Vinicio Teixeira Andrade (2023)
Power electronics is key to the decarbonization process. Converters allow the integration of renewable sources, electrification of cars, and will be essential in the process of electrification of airplanes and other means of transportation. The central component of these converters are transistors. Traditionally manufactured in silicon (Si), two technologies stood out: the MOSFET for low voltage applications and the IGBT for medium voltage applications. In recent years, the development of transistors with wide band gap (WBG) materials, mainly silicon carbide (SiC) and gallium nitride (GaN), which have better performance than silicon components, has changed this scenario. SiC has made MOSFET technology viable at the same voltage levels as the IGBT. However, despite the improved performance, the use of WBG devices still faces challenges in terms of high cost and availability of components. In order to take advantage of the MOSFET SiC at a lower cost. This paper presents a study about the implementation of a 1200V hybrid switch. It is composed of a Si IGBT and a SiC MOSFET in parallel. In this way, a smaller and consequently cheaper SiC is used in parallel with the IGBT, which can be used to create a higher power converter at a lower cost. The technology also allows the advantages of the IGBT to be exploited. The work focuses on which diode to use to complete the hybrid switch, the SiC MOSFET body diode or a discrete diode considering. Three different diode technologies are tested: SiC Schottky diode; ultrafast Si diode; and Gallium Arsenide(GaAs) diode, characterizing the switch with all technologies. In a second step, the work focuses on the dynamics of the IGBT switching at zero voltage when a switching sequence is used to operate the hybrid switch, showing the effects on the current and losses of the hybrid switch. Finally the results are used to calculate the losses of the proposed hybrid switch in a 540 V/30 kW inverter for performance to evaluate performance in a real application.